Quality of Life, Attitude to the Disease, Commitment to the Treatment of Patients with Chronic Tonsillitis - Anton A. Belousov; Alexey N. Khrabrikov; Vladislav A. Sotnikov; Vera B. Nikishina (Lomonosov Moscow State University, 2024)
Background. Outpatient observation, general principles in the treatment of chronic tonsillitis do not lead to a decrease in the incidence of this pathology as well as of other diseases of related nosologies. It is necessary to study the quality of life, attitude to the disease, adherence to treatment of patients with chronic tonsillitis to improve the effectiveness of interaction in the "doctor-patient" tandem. Objective. The aim is to study the parameters of quality of life, type of attitude towards the disease, adherence to treatment in patients with different forms of chronic tonsillitis. Study Participants. A total of 229 patients with chronic tonsillitis (67 men, 162 women, aged 18 to 63 years, average age 31.68 years, standard deviation 0.23 years) participated in the study. Of these, 76 people had a compensated form (14 men, 62 women), 153 people had a decompensated form of chronic tonsillitis (53 men, 100 women). Methods. WHO Brief Questionnaire for Assessing Quality of Life, the "Type of Attitude to Disease (TOBOL)" method, the Russian universal questionnaire for the quantitative assessment of adherence to treatment (KOP-25). Results. Patients with decompensated chronic tonsillitis, which has more severe clinical manifestations, perceive the symptoms of the disease through withdrawal into work, which is manifested in partial ignoring of symptoms and the desire to continue active work. As a result, they have low adherence to treatment in most of its manifestations. In patients with compensated chronic tonsillitis, which is characterized by less severe clinical manifestations of the disease, denial of the disease prevails. However, they have a relatively high adherence to treatment in many of its manifestations. Quality of life indicators are significantly lower in them as compared to those in patients with a decompensated form. Conclusions. Patients with compensated chronic tonsillitis are characterized by denial of the disease, and lower quality of life indicators. However, they show higher adherence to treatment. Patients with decompensated chronic tonsillitis are characterized by withdrawal from the disease to work, low adherence to treatment, and high quality of life indicators. Practical application of the results. The obtained results make it possible to justify elaboration of programmes for the work of a medical psychologist with patients suffering from chronic tonsillitis, and to organize interaction depending on the form of the disease.